Between cultural relativism and liberal ethnocentrism: What does Saudi Arabia tell us about cultural variation in moral identity and prejudice?. Issue 4 (3rd March 2021) - AlSheddi, Mona; Russell, Pascale Sophie; Hegarty, Peter
Abstract: Cultural conceptions of morality are grounded in diverse moral foundations, but moral identity research often assumes that individualizing concerns are the universal basis for morality. Moral identity scales grounded only in individualizing foundations risk liberal ethnocentrism, to the extent that binding foundations emphasized in collectivist cultures are overlooked. Three hundred and ninety‐five Saudi Arabian and UK participants completed prejudice and moral identity measures, which either narrowly measured only individualizing foundations or broadly measured both binding and individualizing foundations. The broader measure had greater power to predict prejudice scores in both countries, particularly in Saudi Arabia. Generally, moral identities grounded in individualizing foundations predicted less prejudice, while moral identities grounded in binding foundations predicted higher prejudice in both countries. Individualizing measures of moral identity may assess ethnocentric concepts, but recognizing morality grounded in binding considerations may taint the category of moral identity with self‐concepts that are associated with greater—not less—ethnocentrism.